Innovative Library Liaison Assessment Activities: Supporting the Scientist's Need to Evaluate Publishing Strategies. - Mylene Ouimette (Issues in Science and Technology Librarianship)
The NIST Research Library's Lab Liaisons conducted an assessment of NIST-authored publications within a specific organizational unit. This assessment used commonly existing information tools, including Journal Citation Reports and the WorldCat database, to evaluate the projected impact of NIST research products within their respective technical communities. The results of this analysis were provided to upper-level NIST technical management to assist in the creation of an overall publications management strategy. [ABSTRACT FROM AUTHOR]